Exploration Of Demotivating Factors in English Language Learning Moodle-Based: Comparison Online and Hybrid Learning - Prasetya, Rizky Eka; Raharjo, Didik Hariyadi (English Education: Jurnal Tadris Bahasa Inggris, 2023)
This study examines demotivating factors in Moodle-based online and hybrid English language learning environments and proposes strategies to overcome them. A mixed-methods approach combining a cross-sectional survey and qualitative interviews was used. A modified Likert-scale questionnaire assessed demotivation and attitude, while e-interviews were conducted with 30 randomly chosen volunteer students in three group sessions to gain insights into their perceptions. Quantitative findings indicate that online learning exhibits higher demotivation levels compared to hybrid learning for English language acquisition. Half of the participants reported feeling somewhat demotivated, while the other half showed solid or low willingness to study English as a foreign language. Qualitative analysis revealed unsuccessful online learning experiences, challenges in the online class environment, inadequate course materials, and lack of interest as significant demotivating factors impacting student engagement in Moodle-based online learning. To enhance online and hybrid course design, English lecturers should address these demotivating factors and incorporate activities that promote learner motivation and proficiency development. This more concise version provides an overview of the study's focus, methods used, and key findings related to demotivating factors in Moodle-based online and hybrid English language learning environments